Hubungan antara Turnover Intention dengan Motivasi Kerja Perawat di Ruang Intensive Care RS X - Reggyna Alfiani; Popon Haryeti; Ayu Prameswari Kusuma Astuti (Khatulistiwa Nursing Journal, 2026)
Background: Turnover intention is the desire to leave one’s job due to high workload, stress, and low job satisfaction, which poses a risk of reducing experienced human resources and lowering work motivation. Low motivation can affect the quality of service. Objective: This study aims to determine the relationship between turnover intention and work motivation among nurses in the intensive care unit of RS X. Methods: This research uses a quantitative design with a cross-sectional approach. The sample was obtained using a total sampling technique, consisting of all nurses working in the ICU, NICU, and HCCU of RS X, totaling 60 respondents. The instruments used were the turnover intention questionnaire and the work motivation questionnaire. Data were analyzed using univariate and bivariate methods with the Spearman correlation test. Results: The results showed a weak but statistically significant negative relationship between turnover intention and work motivation among nurses (r = -0,327; p = 0,011). This indicates that the higher the nurses' turnover intention, the lower their work motivation tends to be. Conclusion: There is a significant relationship between turnover intention and nurses’ work motivation.